Konsep Tarbiyah Menurut Ibnu Taimiyyah: Studi Filosofis tentang Fondasi Keimanan, Akhlak, dan Pembiasaan dalam Pendidikan Islam - Adi Kusmanto; Nasrulloh; Maftuh; Hartoyo (Al-Mudarris, 2026)
This study examines the concept of tarbiyah in the educational thought of Ibn Taymiyyah and analyzes its philosophical foundations within the broader context of Islamic intellectual history. Using a qualitative library research design, the study analyzes key primary texts, particularly Majmu‘ al-Fatawa and Kitab al-Iman, alongside relevant contemporary scholarship. The findings reveal that Ibn Taymiyyah’s concept of tarbiyah constitutes an integrative educational model grounded in tawhid, moral character formation (akhlaq), and habituation as a practical mechanism for ethical development. Unlike approaches that emphasize mystical or speculative dimensions of education, his framework is rooted in scriptural authority and practical moral discipline, reflecting a critical stance toward speculative theology (kalam). This study argues that Ibn Taymiyyah’s educational thought offers a coherent philosophical framework that integrates theological belief, ethical formation, and social practice. Theoretically, it contributes to the reconceptualization of Islamic education as a holistic system that connects faith, knowledge, and action. Practically, the framework provides insights for contemporary Islamic education, particularly in developing value-based curricula, character education, and holistic assessment models that integrate cognitive, moral, and spiritual dimensions.